Model Sistem Informasi Manajemen Sekolah Berbasiskan Notasi Unified Modeling Language - Kurniawan, Yohannes (ComTech: Computer, Mathematics and Engineering Applications, 2013)
Basically the use of integrated information systems can be applied not only for the company, but also education industry, particularly schools. To support business processes at the school, this research would like to describe a conceptual model of information systems using the Unified Modeling Language (UML) notationwith "4 +1 View" architectural model. This model is expected to assist analysis and design the whole business processes at school. A conceptual model of the information system can help application developers to easily and clearly understand the school system. By adopting this information system model, schools are able to have effective understanding of management information systems.